2008
DOI: 10.1056/nejmoa0801297
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Aspirin or Resistant Starch on Colorectal Neoplasia in the Lynch Syndrome

Abstract: T h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 359;24 www.nejm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
179
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(187 citation statements)
references
References 21 publications
3
179
2
3
Order By: Relevance
“…There is good evidence (level 1b) that medical therapy with aspirin reduces CRC risk in patients with Lynch syndrome. A recent randomized clinical trial (RCT) showed a significant reduction in CRC and other cancers among Lynch syndrome patients who received aspirin 600 mg (Burn et al, 2008;Burn et al, 2011;Chan et al, 2012). A subsequent meta-analysis examining daily aspirin use and its effect on cancer revealed a reduced risk of CRC mortality among aspirin-treated patients, although no greater benefit was achieved with an aspirin dosage above 75 mg daily .…”
Section: Rev Ised Bethesda Guidelinesmentioning
confidence: 99%
“…There is good evidence (level 1b) that medical therapy with aspirin reduces CRC risk in patients with Lynch syndrome. A recent randomized clinical trial (RCT) showed a significant reduction in CRC and other cancers among Lynch syndrome patients who received aspirin 600 mg (Burn et al, 2008;Burn et al, 2011;Chan et al, 2012). A subsequent meta-analysis examining daily aspirin use and its effect on cancer revealed a reduced risk of CRC mortality among aspirin-treated patients, although no greater benefit was achieved with an aspirin dosage above 75 mg daily .…”
Section: Rev Ised Bethesda Guidelinesmentioning
confidence: 99%
“…To date, there are two controlled randomized trials that primarily evaluated the efficacy of aspirin in high-risk CRC patients: the Colorectal Adenoma/Carcinoma Programme (CAPP)1 [22] , which included 206 young individuals with a diagnosis of familial adenomatous polyposis (FAP), and CAPP2 [23] , which studied 1009 patients with Lynch syndrome. Both studies compared aspirin (600 mg/d), with or without resistant starch or resistant starch placebo.…”
Section: Clinical Effects Of Aspirin In High-risk Populations: Familimentioning
confidence: 99%
“…Several compounds have been suggested including anti-inflammatory agents such as aspirin, which has been shown to reduce the risk of cancer in LS (30). Tumor-maturing agents such as retinoids and, more recently, checkpoint inhibitors can be considered as "tumor preventive tools."…”
Section: Therapeutic Considerationsmentioning
confidence: 99%